مدى توافر أسس إدارة الجودة الشاملة في الجامعات الليبية من وجهة نظر الأكاديميين الليبيين الدارسين بماليزيا - Abdullah Abdul Karim Mohammed
This research aims to study the availability of the basic principles of Total Quality Management (TQM) at the Libyan universities from the perspective of The Libyan Academics studying in Malaysia, and seeks their suggestions for the development of the administrative process at Libyan Universities. The researcher supposed there are no substantial differences in the perspective between the participants attributed to the demographic variables of the study: (gender, age, qualification, Career, and the experience). The Questionnaire was adopted as a tool to collecting the data from the study sample consisted of (198) Academic with response rate (90%). In order to achieve the objectives of the study, the researcher using a set of indicators, statistical analysis (Mann Whitney and Kruskal test) to test the hypotheses, and therefore, the finding indicated that the basic principles of (TQM) in Libyan universities are available with a very low degree, with variations in the perspective of academics on this result attributable to the participant’s age, qualification, job and experience. The academics confirmed the importance of development and restructuring of administrative systems at the Libyan universities, which can lead to adoption and application of the modern management concepts. In light of the previous findings, the researcher made recommendations to competent authorities about the necessary of change the regulations and legislation in the Libyan universities; with granted sufficient flexibility in order to keep pace with developments in the environmental variables surrounding. Furthermore, the researcher recommended the importance of the provision of financial resources, supplies and facilities to raising the quality of academic services at Libyan universities, in addition to creating assessment and measurement basis commensurate with the requirements of the educational process at Libyan universities, to ensure better academic practices in order to increase efficiency. Finally, this study provides a set of points can be adopted by the competent authorities and future studies when they study the obstacles that hinder the effective application of the total quality management and improve the quality of educational services in the Libyan universities.